Prognostic Factors of Cervical Cord Injury - MADOUGOU, Souimaïla; LAWSON, ERIC; ALIHONOU, THIERRY; CHIGBLO, SÈGLA PASCAL ERIC; GBEDINHESSI, C.; GANDAHO, HUGUES JEAN-THIERRY; HODE, LUPHIN; HANS MOEVI, ARISTOTE (My University, 2017)
Aim: Identify prognostic factors of management of cervical spinal cord injury in a low income country. Patients and method: This was a retrospective descriptive study which took place over 4 years and half, from 1st January 2010 to 30 June 2014. A correlation with statistical test has been searched between different variables: sex and clinical evolution, age and clinical evolution, injury circumstances and neurological achievement, admission delay and clinical evolution, operative delay and clinical evolution, tetraplegia and clinical evolution, sphincter disorders and clinical evolution. Epi-info version 3. 5. 1. has been used for statistical tests. Results: Women had clinical improvement in 72.7% and men in 56.5% with a statistically not significant difference (p=0.6053). Patients under 49 years old had a clinical improvement in more than 50% while patients of 50-59 years old have all presented an improvement with a statistically not significant difference (p=0.3665). 4 patients among 7 (57.1%) with a neurological improvement were victims of a public highway accident and 3 patients (42.9%) of work accident with a statistically not significant difference (p=0.4567). A clinical improvement was obtained in more than 50% of patients whatever is the admission delay with a statistically not significant difference (p= 0.4321). Clinical improvement concerned 15 patients (75%) among 20 patients with surgical management after 48 hours with a statistically significant difference (0.0029). 53.8% of patients with incomplete tetraplegia had a clinically improvement with a statistically significant difference (p=0.0378). Clinical improvement was achieved in 68.8% of patients without sphincter disorders against 48% in patients with sphincter disorders. Difference was statistically significant (p=0.0083) Conclusion: At the end of this study, there is a significant clinical improvement in patients with surgical management after 48 years, in patients with incomplete tetraplegia and patients without sphincter disorders.
Keywords: Prognostic; Factors; injury; Cervical; Cord